Plastic Waste Management Strategies to Reduce Negative Impacts on the Environment and Human Health in Padang City - Lieza Corsita; Mila Sari; Satiti Kawuri Putri (Miracle Journal Get Press, 2024)
Plastic waste has become one of the major problems threatening the environment and human healthIn Indonesia, the use of plastics in daily life, such as shopping bags, water bottles, and food packaging, contributes greatly to the increasing amount of plastic waste (Ditjen PPKL, 2018). This research aims to analyse effective plastic waste management strategies to reduce negative impacts on the environment. The research uses a mixed-method approach, a combination of quantitative and qualitative methods, to gain a comprehensive understanding of the condition of plastic waste and identify the factors that influence the effectiveness of such management. This method is relevant for evaluating waste management policies, the role of the community, and the application of environmentally friendly technologies. This study will be conducted in several areas that have high plastic waste production rates, such as urban, coastal, and areas with community-based waste management initiatives. The results show that community awareness level participation in recycling high 60% p = 0.001 This shows that environmental education is very important to increase community participation. Community-based education is needed to raise this awareness. A massive education campaign is needed, involving community leaders to strengthen positive social norms.